VO2-based radiative thermal transistor with a semi-transparent base. (May 2018) - Prod'homme, Hugo; Ordonez-Miranda, Jose; Ezzahri, Younès; Drévillon, Jérémie; Joulain, Karl
Highlights: We study a radiative thermal transistor made of two plates of SiO2 surrounding a plate of VO2 exhibiting an insulator to metal transition. We calculate all radiative thermal fluxes in the transistor by means of fluctuational electrodynamics in both near and far field and in the case of an opaque or semi-transparent VO2 plate. Two regimes are exhibited: an amplification regime and a switching regime. An optimized configuration for the modulation efficiency is identified in terms of the separation distance between the plates and of the VO2 plate thickness. Abstract: We study a radiative thermal transistor analogous to an electronic one made of a VO2 base placed between two silica semi-infinite plates playing the roles of the transistor collector and emitter. The fact that VO2 exhibits an insulator to metal transition is exploited to modulate and/or amplify heat fluxes between the emitter and the collector, by applying a thermal current on the VO2 base. We extend the work of precedent studies considering the case where the base can be semi-transparent so that heat can be exchanged directly between the collector and the emitter. Both near and far field cases are considered leading to 4 typical regimes resulting from the fact that the emitter-base and base-collector separation distances can be larger or smaller than the thermal wavelength for a VO2 layer opaque or semi-transparent. Thermal currents variations with the base temperatures are calculated and analyzed. It is found that the transistor can operate in an amplification mode as already stated in [1] or in a switching mode as seen in[2] . An optimum configuration for the base thickness and separation distance maximizing the thermal transistor modulation factor is found.